Analysis of Marketing Strategy in Facing Business Competition: Study at the Lesehan Oha Doku Restaurant in Dompu - Fazriah, Khafilah; Jumaidi, Lalu Takdir (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to analyze the marketing strategy of Lesehan Oha Doku Restaurant in Dompu using a descriptive qualitative approach. Data were collected through observation and in-depth interviews at the research location with the owner, Mrs. Kartini Fauzan. The results show that Lesehan Oha Doku Restaurant successfully utilizes social media such as Facebook, Instagram, and WhatsApp to increase visibility and reach a wider consumer base. Engaging content showcasing the unique dishes and bamboo-woven restaurant concept, along with active customer interaction, has built strong relationships and increased customer loyalty. Additionally, product diversification through catering services and strong branding with the name "Lesehan Oha Doku," which reflects local cultural identity, contributes to its success. Cultural marketing that integrates local elements has proven effective in creating an authentic experience for customers. SWOT analysis reveals strengths in quality ingredients, strategic location, and effective digital marketing strategies, despite challenges in human resources and price competition. This combination of strategies has enabled Lesehan Oha Doku Restaurant to outperform competitors in the Dompu culinary market and continue to grow rapidly.